Socio-economic impacts of climate change on indigenous communities in the save valley area of Chipinge district, Zimbabwe - Sithole, Portia Kimberley; Mawere, Munyaradzi; Mubaya, Tapuwa Raymond (Frontiers in Environmental Economics, 2023)
In recent years, climate change has fast become a reality that warrants concerted action from stakeholders across fields. Communities in the Save Valley Area of Chipinge District of Manicaland Province in Zimbabwe, for example, report high incidences of socio-economic disruptions caused by climate change. These include loss of livelihoods, livestock, crops, food stocks and infrastructure damage. This study investigated the coping mechanisms adopted by communities in the Save Valley Area in their attempt to mitigate the socio-economic vagaries of climate change. In order to understand community perceptions regarding the possible link between climate change and the increased frequency and intensity of flooding incidences and to evaluate the evolution of community disaster risk management and resilience building as a function of changing climatic realities, the study employed the mixed method research design. Resettled farming households in the Middle Sabi, communal farming households in Chibuwe and Tongogara areas and members of the Chipinge District Development Committee were sampled for this study. Questionnaires, transact walks, structured interviews and focus group discussions were the main data collection methods utilized. Quantitative data entry was done via the Statistical Package for Social Sciences (SPSS) software. Qualitative data was coded and analyzed thematically. Findings revealed that climate change has heightened community vulnerability, weakened their adaptive capacities, as well as disrupting the community resilience-building initiatives. In turn, communities have made attempts to respond to the challenges arising from climate change by modifying their socio-economic activities, organizing themselves internally and reverting to the use of indigenous knowledge based interventions.